N-formimidoyl thienamycin (MK0787): in vitro activity against anaerobic bacteria. - Martin, D A (1982)
The in vitro activity of N-formimidoyl thienamycin (MK0787) was tested against 239 anaerobic bacteria clinical isolates: 70 of Bacteroides fragilis, 18 of B. distasonis, 16 of B. thetaiotaomicron, 10 of B. vulgatus, 24 of Bacteroides spp., 22 of B. melaninogenicus (all three subspecies), 26 of Fusobacterium spp., 10 of Peptococcus spp., 15 of Peptostreptococcus spp., 15 of Clostridium perfringens, and 13 of Clostridium spp. Ninety-five percent of the isolates were inhibited by less than or equal to 0.125 microgram/ml, and all were inhibited by less than or equal to 4 micrograms/ml.